Tari Maena Sebagai Media Pemberitaan Injil dalam Kearifan Budaya Nias - Lestari Loi (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
This research aims to explore the deep meaning of the Maena dance as a means of spreading the Gospel among the people of Nias. This research applies a qualitative approach with ethnographic methods. The research process began with a comprehensive literature study regarding Maena dance, Christianity in Nias, as well as studies related to performing arts as a communication medium. Through this step, the researcher seeks to gain a comprehensive understanding of the historical, social, cultural and theological context of the phenomenon under study. Maena Dance is a cultural heritage from Nias that is rich in traditional values, and also has great potential as a means of conveying the Gospel. Through a creative and contextual approach, Maena Dance has succeeded in integrating Christian symbols, Biblical values ​​and spiritual messages into its movements, costumes and poetry. In this way, Maena becomes an effective communication medium for conveying the Gospel message to the community, especially in environments that still value local traditions.